2022
DOI: 10.1111/cpf.12742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pneumoperitoneum and Trendelenburg position on internal carotid artery blood flow measured by ultrasound during robotic prostatectomy

Abstract: Introduction Robotic prostatectomy requires pneumoperitoneum and a steep Trendelenburg position; however, this condition may compromise cerebral blood flow. Here, we evaluated the effect of pneumoperitoneum and the steep Trendelenburg position on internal carotid artery (ICA) blood flow measured by Doppler ultrasound during robotic prostatectomy. Methods Patients who underwent robotic prostatectomy were prospectively recruited. The ICA blood flow was measured at the following five time‐points: with the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Removing the small intestine from the pelvic cavity is important to obtain a clear view and to avoid inadvertent contact with the intestine during surgery. However, the steep Trendelenburg position has been reported to be associated with complications such as gas embolism, 1 increased intraocular pressure, [2][3][4] increased intracranial pressure, 5,6 decreased blood flow in the internal carotid artery, 7 spontaneous otorrhea, 8 upper-body complications, 9 nerve injury, 10,11 peripheral neuropathy, 12 venous thromboembolism, 13,14 and lower-extremity compartment syndrome caused by impaired blood flow. 15 Gould et al previously reported that a mean Trendelenburg angle of 28.0 was required to complete robotic gynecologic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Removing the small intestine from the pelvic cavity is important to obtain a clear view and to avoid inadvertent contact with the intestine during surgery. However, the steep Trendelenburg position has been reported to be associated with complications such as gas embolism, 1 increased intraocular pressure, [2][3][4] increased intracranial pressure, 5,6 decreased blood flow in the internal carotid artery, 7 spontaneous otorrhea, 8 upper-body complications, 9 nerve injury, 10,11 peripheral neuropathy, 12 venous thromboembolism, 13,14 and lower-extremity compartment syndrome caused by impaired blood flow. 15 Gould et al previously reported that a mean Trendelenburg angle of 28.0 was required to complete robotic gynecologic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the arterial system, the internal carotid artery (ICA) underwent no significant changes between supine and upright position on MRI [48]. According to Montero et al [59], the ICA and vertebral artery diameter increased in TB on US (n = 10), but this increase was not found by Yu et al (n = 28) [60]. No change in ICA or vertebral artery diameter was seen in R-TB position compared to supine [59].…”
Section: Head-neckmentioning
confidence: 94%
“…In the arterial system, the internal carotid artery (ICA) underwent no significant changes between supine and upright position on MRI 46 . According to Montero et al 57 the ICA and vertebral artery diameter increased in TB on US (n=10), but this increase was not found by Yu et al (n=28) 58 . No change in ICA or vertebral artery diameter was seen in R-TB position compared to supine 57 .…”
Section: Head-neckmentioning
confidence: 85%
“…Currently, the ESVS 2019 AAA guideline recommends EVAR as preferred treatment option in most AAA patients with suitable anatomy and reasonable life expectancy while OSR is considered preferred treatment in patients with long life expectancy 4 . Contrastingly, the English National Institute for Health and Care Excellence (NICE) advices to consider EVAR only in cases that have increased anesthetic, medical or anatomical risks for OSR 58 . The statement of NICE to disregard EVAR was made even more boldly in an earlier draft version of the document 59 .…”
Section: Room For Improvement?mentioning
confidence: 99%